Pengaruh Penggunaan Artificial Intelligence (AI) Terhadap Kinerja Perusahaan Penerbitan Buku di Kota Bandung - Kalifatullah Ermaya, Sir; Nur Laela Ermaya, Husnah; Ummul Umara, Yara; El Farras, Nurussyafiqa (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study aims to measure and analyze the effect of the use of Artificial Intelligence (AI) on company performance using a quantitative approach in thirty businesses engaged in book publishing in the city of Bandung. From the results of the study, it can be concluded that the use of AI has a positive effect on company performance. AI-based analysis plays an important role in supporting companies to enter new markets. In addition, the implementation of AI within an organization can reduce operational time and costs. Therefore, companies should be able to improve the quality of their human resources in adopting the ever-evolving AI technology. In addition, companies can also use AI gradually, considering that the use of this technology requires a lot of investment costs.